#### Answer

Simplified=8

#### Work Step by Step

$\frac{16+3(2)^{4}}{12-(10-6)}$
$=\frac{16+3(16)}{12-(4)}$
$=\frac{16+48}{8}$
$=\frac{64}{8}$
$=8$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

Simplified=8

$\frac{16+3(2)^{4}}{12-(10-6)}$
$=\frac{16+3(16)}{12-(4)}$
$=\frac{16+48}{8}$
$=\frac{64}{8}$
$=8$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.